Implementation of the Principles of Amanah , Adl , and maslahah in the Business Ethics of Digital Start-ups: An Islamic Economic Perspective - Hidayatullah (Journal of Islamic Economics Perspectives, 2026)
The rapid expansion of Indonesia's digital start-up ecosystem has created substantial economic opportunities while simultaneously intensifying ethical challenges related to data governance, equitable value distribution, and public welfare. Existing studies have largely examined Islamic business ethics through isolated ethical principles, leaving limited understanding of how the principles of amanah (trustworthiness), Adl (justice), and  maslahah  (public benefit) interact as an integrated ethical framework for sustainable digital entrepreneurship. This study aims to analyze the implementation of these three principles within Indonesia's digital start-up ecosystem and to develop a conceptual model explaining their contribution to sustainable business governance. The study employs a qualitative descriptive design using a library research approach, integrating normative analyses of the Qur'an, Hadith, classical Islamic jurisprudence, contemporary Islamic economics literature, and empirical reports on Indonesia's digital business ecosystem through qualitative content analysis. The findings demonstrate that amanah provides the ethical foundation for transparent data governance and organizational accountability, Adl guides equitable pricing, stakeholder protection, and fair value distribution, while  maslahah  directs innovation toward long-term social welfare. More importantly, the analysis reveals that these principles operate as an interconnected ethical system rather than as independent normative values, leading to the formulation of the Islamic Digital Business Model (IDBM), which integrates ethical governance, operational justice, and social impact into a unified framework for digital entrepreneurship. This study extends existing Islamic business ethics literature by offering a theoretically integrated framework that strengthens discussions on Islamic digital governance, sustainable entrepreneurship, and maq??id-oriented business development in contemporary digital economies.